Pear production in Brazil: a review - Luz A.R.* (2021)
© 2021 Federal University ofPiauI. All rights reserved.The cultivation of pear trees in Brazil started with a larger harvested area than apple trees, however, it did not have the same development. The production of pears has not been as promising as expected, being considered one of the temperate-climate fruits of less commercial interest in Brazil, due to several factors that are discussed in this paper. However, the pear has great economic importance in Brazil as it is the main item in the Brazilian fresh fruit import agenda. Aspects related to the main scientific advances and applied technologies are also described in this paper, mainly regarding rootstocks, cultivars, management techniques and, finally, some considerations about what is missing to produce more pears in Brazil.